AB0723 Evaluation of MRI Changes in Patients with Ankylosing Spondylitis and their Correlation with Clinical and Functional Impairment at Different Disease Duration. (10th June 2014) - Kovalenko, S.; Protsenko, G.; Kachur, V.; Ivanova, K.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory rheumatic disease. Magnetic resonance imaging (MRI) is currently used not only to facilitate early diagnosis of the AS, but also to monitor the course of inflammation. Objectives: To evaluate the differences in clinical and functional impairment for different duration of the disease in AS patients with and without of active inflammation on MRI. Methods: Study involved 40 people (males) with AS and disease duration <10 years and >10 years. The patients were divided into two groups: Group I – patients without inflammation on MRI or with postinflammatory changes (20 people), Group II – patients with inflammation on MRI (20 people). All evaluation parameters: 10-point assessment of mobility of the spine in the cervical (neck rotation), thoracic (lateral flexion), lumbar parts (modified Schober test), indexes BASMI, BASDAI. All patients underwent MRI of sacroiliac joints and the spine. Results: Between groups 1 (without inflammation on MRI) and 2 (with inflammation on MRI) were obtained following differences: index BASDAI: <10 years disease duration: 4, 10±1, 0 vs 4, 03±0, 48; >10 years of disease duration: 2, 36±0, 40 vs 3, 92±0, 35 (p<0, 05). Mobility in the cervical parts of spine: <10 years disease duration: 2, 75±0, 47 vs 5, 22±0, 52 (p<0, 05); >10 years disease duration: 7, 49±0, 46 vs 7, 40±0, 35. Mobility in the thoracic parts of spine: <10 years disease duration: 3, 50±0, 28 vs 6, 22±0, 72 (p<0, 05); >10 years disease duration: 8, 50±0, 39 vs 8, 60±0, 65. Mobility in the lumbar parts of spine: <10 years disease duration: 5, 75±0, 25 vs 8, 55±0, 50 (p<0, 05); >10 years disease duration: 9, 81±0, 34 vs 9, 40±0, 55. Index BASMI: <10 years disease duration: 2, 60±0, 41 vs 4, 38±0, 38 (p<0, 05); >10 years disease duration: 6, 06±0, 25 vs 5, 92±0, 41. Conclusions: In patients with active inflammation on MRI mobility impairments were significantly higher in all parts of the spine in the early stages of the disease (up to 10 years AS duration), and disease activity was significantly higher than in patients without osteitis at disease duration over 10 years. This indicates a lower quality of life for patients with active inflammation on MRI as on the early so on the late stages of the disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2663